Cleavage of TANK-Binding Kinase 1 by HIV-1 Protease Triggers Viral Innate Immune Evasion - Jeremiah, Sundararaj Stanleyraj; Miyakawa, Kei; Matsunaga, Satoko; Nishi, Mayuko; Kudoh, Ayumi; Takaoka, Akinori; Sawasaki, Tatsuya; Ryo, Akihide (Frontiers in Microbiology, 2021)
Type-I interferons (IFN-I) are the innate immune system’s principal defense against viral infections. Human immunodeficiency virus-1 (HIV-1) has evolved several ways to suppress or evade the host’s innate immunity in order to survive and replicate to sustain infection. Suppression of IFN-I is one among the multiple escape strategies used by HIV-1 to prevent its clearance. HIV-1 protease which helps in viral maturation has also been observed to cleave host cellular protein kinases. In this study we performed a comprehensive screening of a human kinase library using AlphaScreen assay and identified that TANK binding kinase-1 (TBK1) was cleaved by HIV-1 protease (PR). We demonstrate that PR cleaved TBK1 fails to phosphorylate IFN regulatory factor 3 (IRF3), thereby reducing the IFN-I promoter activity and further reveal that the PR mediated suppression of IFN-I could be counteracted by protease inhibitors (PI) in vitro. We have also revealed that mutations of HIV-1 PR that confer drug resistance to PIs reduce the enzyme’s ability to cleave TBK1. The findings of this study unearth a direct link between HIV-1 PR activity and evasion of innate immunity by the virus, the possible physiological relevance of which warrants to be determined.